Preparation, characterization and luminescence properties of core–shell ternary terbium composites SiO2(600)@Tb(MABA-Si)L. Issue 3 (14th March 2018) - Ma, Yang-Yang; Li, Wen-Xian; Zheng, Yu-Shan; Bao, Jin-Rong; Li, Yi-Lian; Feng, Li-Na; Yang, Kui-Suo; Qiao, Yan; Wu, An-Ping
Abstract : Two novel core–shell structure ternary terbium composites SiO2(600) @Tb(MABA-Si)·L(L:dipy/phen) nanometre luminescence materials were prepared by ternary terbium complexes Tb(MABA-Si)·L2 ·(ClO4 )3 ·2H2 O shell grafted onto the surface of SiO2 microspheres. And corresponding ternary terbium complexes were synthesized using (CONH(CH2 )3 Si(OCH2 CH3 )3 )2 (denoted as MABA-Si) as first ligand and L as second ligand coordinated with terbium perchlorate. The as-synthesized products were characterized by means of IR spectra, 1 HNMR, element analysis, molar conductivity, SEM and TEM. It was found that the first ligand MABA-Si of terbium ternary complex hydrolysed to generate the Si–OH and the Si–OH condensate with the Si–OH on the surface of SiO2 microspheres; then ligand MABA-Si grafted onto the surface of SiO2 microspheres. The diameter of SiO2 core of SiO2(600) @Tb(MABA-Si)·L was approximately 600 nm. Interestingly, the luminescence properties demonstrate that the two core–shell structure ternary terbium composites SiO2(600) Tb(MABA-Si)·L(dipy/phen) exhibit strong emission intensities, which are 2.49 and 3.35 times higher than that of the corresponding complexes Tb(MABA-Si)·L2 ·(ClO4 )3 ·2H2 O, respectively. Luminescence decay curves show that core–shell structure ternary terbium composites have longer lifetime. Excellent luminescence properties enable the core–shell materials to have potential applications in medicine, industry, luminescent fibres and various biomaterials fields.